2018
DOI: 10.1136/annrheumdis-2017-212639
|View full text |Cite
|
Sign up to set email alerts
|

Low miR200b-5p levels in minor salivary glands: a novel molecular marker predicting lymphoma development in patients with Sjögren’s syndrome

Abstract: These findings support that miR200b-5p levels in MSGs represent a novel predictive and possibly pathogenetic mechanism-related factor for the development of SS-associated NHL, since its expression is impaired years before lymphoma clinical onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Therefore, it is not surprising that mir142 was highly expressed in highly infiltrating TMEs . Moreover, miR‐223, mir155, mir187, and mir200b have also been reported to be associated with the immune response, so it will be worthwhile to conduct more research exploring the relationships between noncoding RNAs and the immune response in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that mir142 was highly expressed in highly infiltrating TMEs . Moreover, miR‐223, mir155, mir187, and mir200b have also been reported to be associated with the immune response, so it will be worthwhile to conduct more research exploring the relationships between noncoding RNAs and the immune response in the future.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA200b-5p and thymic stromal lymphopoietin (TSLP) [89,90]. In a very recent paper [91], low miRNA200b-5p was reduced in prelymphoma and lymphoma pSS patients, proving to be a useful predictor. TSLP increases in the serum of pSS patients, with higher levels in the myoepithelial sialadenitis and mixed cryoglobulinemia, and with the highest level in patients with B-cell lymphoma [92].…”
Section: Laboratory Biomarkers Will Be Crucial To Improve Lymphoma Prmentioning
confidence: 99%
“…Significantly lower levels of miR200b‐5p, a miRNA which regulates expression of autoantibodies directed to intracellular autoantigens, La/SSB, were characterized in SS patients with MALT lymphoma compared with those without ( p < 0.05; Gourzi, Kapsogeorgou, Kyriakidis, & Tzioufas, ). Similarly, in the study of Kapsogeorgou, Papageorgiou, Protogerou, Voulgarelis, and Tzioufas (), miR200b‐5p was significantly downregulated in patients with SS who would develop or had NHL, and was able to discriminate this subset ( p < 0.0001) from those without lymphoma or those with non‐SS sialadenitis. These investigators reported miR200b‐5p as a strong independent predictor of patients who would develop NHL.…”
Section: Resultsmentioning
confidence: 78%
“…Significantly lower levels of miR200b-5p, a miRNA which regulates expression of autoantibodies directed to intracellular autoantigens, La/ SSB, were characterized in SS patients with MALT lymphoma compared with those without (p < 0.05; Gourzi, Kapsogeorgou, Kyriakidis, & Tzioufas, 2015). Similarly, in the study of Kapsogeorgou, Papageorgiou, Protogerou, Voulgarelis, and Tzioufas (2018) Barone et al (2008) reported that CXCL12 was principally detected in infiltrated ducts and malignant B cells in the salivary glands of patients with SS. Additionally, CXCL12 levels were increased in MALT lymphomas and isolated tumor cells, suggesting the direct involvement of CXCL12 in the organization of ectopic reactive lymphoid tissue and its association with the malignant B-cell component and regulation of malignant B-cell survival.…”
Section: Geneticsmentioning
confidence: 94%